2024
DOI: 10.3390/buildings14051223
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Punching Shear Strength of Steel Fiber-Reinforced Concrete Slabs: A Machine Learning Approach with Data Augmentation and Explainability

Cheng Cheng,
Woubishet Zewdu Taffese,
Tianyu Hu

Abstract: Reinforced concrete slabs are widely used in building structures due to their economic, durable, and aesthetic advantages. The determination of their ultimate strength often hinges on punching shear strength. Presently, methods such as closed hoops, steel bending, and fiber reinforcement are employed to enhance punching shear strength, with fiber reinforcement gaining popularity due to its ease of implementation and efficacy in improving concrete durability. This study introduces a novel approach employing six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The findings indicate that the XGB model exhibited superior robustness and accuracy 21 . At the same time, the problem of small experimental datasets was solved by using an innovative method of data augmentation, facilitating the achievement of a higher prediction accuracy for the punching shear strength of steel fiber-reinforced concrete slabs 22 . Jayasinghe used eight machine-learning models to develop a framework for predicting the shear capacity of recycled aggregate concrete (RAC) beams, and the results revealed that the XGBoost model had the best prediction effect, with the coefficient of determination R 2 on the test set reaching 0.95 (slender beam) and 0.78 (deep beam) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicate that the XGB model exhibited superior robustness and accuracy 21 . At the same time, the problem of small experimental datasets was solved by using an innovative method of data augmentation, facilitating the achievement of a higher prediction accuracy for the punching shear strength of steel fiber-reinforced concrete slabs 22 . Jayasinghe used eight machine-learning models to develop a framework for predicting the shear capacity of recycled aggregate concrete (RAC) beams, and the results revealed that the XGBoost model had the best prediction effect, with the coefficient of determination R 2 on the test set reaching 0.95 (slender beam) and 0.78 (deep beam) 23 .…”
Section: Introductionmentioning
confidence: 99%